Textural, rheological and sensory properties of spreadable processed goat cheese - Laura Burgos; Nora Pece; Silvina Maldonado (International Journal of Food Studies)
The aim of this work was to study the influence of the ripening degree of natural goat cheese on texture, rheological and sensory properties of processed cheese products. Processed cheeses were formulated using goat cheeses with 10, 20, and 40 days of ripening. We obtained four different formulations by varying the proportions of these cheeses in each formulation. The variation in major α, β, and para-κ casein fractions, rheological properties, and the texture of samples were determined, and a sensorial evaluation was carried out. Cheeses from Formulation 2 (50% cheese ripened for 10 days, 25% cheese ripened for 20 days and 25% cheese ripened for 40 days) had greater values of α and β –caseins, which is related to a greater content of intact casein resulting from a cheese with short ripening time. Hardness, adhesiveness and complex modulus (G*) decreased as the degree of ripening of the natural cheese (raw material) increased. Formulation 2 presented a G* value similar to that of the commercial processed cow cheese and the greatest firmness. Formulation 2 presented the characteristics we aimed to obtain, described as spreadable, slightly acid and salty cheese.